2011
DOI: 10.1002/alr.20059
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of tissue remodeling genes in a mouse model of acute allergic rhinitis

Abstract: Background Osteogenesis, fibrosis and scarring are prominent pathologic changes resulting from chronic sinonasal inflammation, and these tissue changes may increase the degree of disease symptomatology and the level of surgical difficulty. Members of the Bone Morphogenetic Protein (BMP) and Fibroblast Growth Factor (FGF) families of cytokines and the Matrix Metalloproteinase (MMP) family of endopeptidases are known to regulate tissue remodeling in other disease processes, but their role in acute and chronic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In the same test, the expression of a range of cytokines from Fibroblast Growth Factors (FGF) and Matrix Metalloproteinases (MMP) was found to be elevated after exposure to a specific allergen. These findings suggest that signal transduction in cells intended for initiating the process of fibrogenesis and remodelling is initiated earlier in inflammatory illnesses [29].…”
Section: The Bmp Protein and Bmpr Receptor: Expression Function And mentioning
confidence: 89%
“…In the same test, the expression of a range of cytokines from Fibroblast Growth Factors (FGF) and Matrix Metalloproteinases (MMP) was found to be elevated after exposure to a specific allergen. These findings suggest that signal transduction in cells intended for initiating the process of fibrogenesis and remodelling is initiated earlier in inflammatory illnesses [29].…”
Section: The Bmp Protein and Bmpr Receptor: Expression Function And mentioning
confidence: 89%
“…Quantitation of the amount of target in samples is done by measuring C t and using the standard curve to determine starting copy number. Calculation of C t s, preparation of a standard curve, determination of the starting copy number, and calculation of statistical significance was performed using the ΔΔC t method with the aid of the SABiosciences PCR Array Data Analysis Web Portal 22. 18S RNA was used as the comparator.…”
Section: Methodsmentioning
confidence: 99%
“…A better understanding of the cellular and molecular processes leading to osteogenesis, fibrosis, and angiogenesis in CRS is needed in order to develop novel therapies aimed at halting or reversing CRS‐associated tissue remodeling. We have previously demonstrated acute changes in several members of the BMP, FGF, and MMP families in a mouse model of acute allergic rhinitis 22. The purpose of this study is to characterize the changes in BMP, FGF, and MMP family expression in a mouse model of CRS.…”
Section: Introductionmentioning
confidence: 96%
“…As with the ion channel genes, the general pattern of remodeling gene expression was similar in the middle ear and inner ear. Previous work has shown that these genes are indeed affected by allergic fungal rhinosinusitis and otitis media in the mouse model 3, 40 . Altered expression of these genes in the inner ear in the chronic OM model has not previously been shown.…”
Section: Discussionmentioning
confidence: 93%